2018
DOI: 10.1074/jbc.ra118.001922
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of cathepsin C inactivation for membrane exposure of proteinase 3, the target antigen in autoimmune vasculitis

Abstract: Membrane-bound proteinase 3 (PR3) is the main target antigen of anti-neutrophil cytoplasmic autoantibodies (ANCA) in granulomatosis with polyangiitis, a systemic small-vessel vasculitis. Binding of ANCA to PR3 triggers neutrophil activation with the secretion of enzymatically active PR3 and related neutrophil serine proteases, thereby contributing to vascular damage. PR3 and related proteases are activated from pro-forms by the lysosomal cysteine protease cathepsin C (CatC) during neutrophil maturation. We hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 59 publications
0
37
1
Order By: Relevance
“… 24 , 25 Loss of function mutations in the CatC gene (gene symbol CTSC ) in humans cause Papillon–Lefèvre syndrome (PLS, OMIM 245000) characterized by a severe prepubertal periodontitis and palmoplantar keratoderma without marked immunodeficiency. 26 , 27 The lack of CatC activity results in an almost total elimination of elastase-related serine proteases in neutrophils from PLS patients 25 , 28 , 29 ( Figure 3 A). Moreover, PLS cells are incapable of producing neutrophil extracellular traps (NETs), networks of fibers, primarily composed of DNA.…”
Section: Pharmacological Inhibition Of Neutrophil Elastase-related Prmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 , 25 Loss of function mutations in the CatC gene (gene symbol CTSC ) in humans cause Papillon–Lefèvre syndrome (PLS, OMIM 245000) characterized by a severe prepubertal periodontitis and palmoplantar keratoderma without marked immunodeficiency. 26 , 27 The lack of CatC activity results in an almost total elimination of elastase-related serine proteases in neutrophils from PLS patients 25 , 28 , 29 ( Figure 3 A). Moreover, PLS cells are incapable of producing neutrophil extracellular traps (NETs), networks of fibers, primarily composed of DNA.…”
Section: Pharmacological Inhibition Of Neutrophil Elastase-related Prmentioning
confidence: 99%
“…The blood samples and pictures were taken after informed consent was obtained, and the study was conducted according to Declaration of Helsinki principles. 29 (B) Pharmacological inactivation of CatC by prolonged administration of IcatC XPZ-01 in a Macaca fascicularis experimental model of acute lung inflammation. The image shows broncho-alveolar lavage of an anesthetized macaque.…”
Section: Pharmacological Inhibition Of Neutrophil Elastase-related Prmentioning
confidence: 99%
“…However, in our patient, cancer developed on the face; this could be either be an incidental finding or cathepsin C may play a role in cancer development. Cook (2009) mentioned that although cathepsin C mutation impaired the cytotoxic lymphocyte activity in PLS, leading to immunodeficiency and the possibility of tumor progression at a cellular level, immunodeficiency was not one of the main clinical features for PLS, as explained by cathepsin C-independent pathways [5, 9]. The role of cathepsin C could be the reason for the multiple cancer cases and severe infections like liver abscess reported in PLS patients [5, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Cook (2009) mentioned that although cathepsin C mutation impaired the cytotoxic lymphocyte activity in PLS, leading to immunodeficiency and the possibility of tumor progression at a cellular level, immunodeficiency was not one of the main clinical features for PLS, as explained by cathepsin C-independent pathways [5, 9]. The role of cathepsin C could be the reason for the multiple cancer cases and severe infections like liver abscess reported in PLS patients [5, 9]. The role of cathepsin C in the development of dermatological conditions in PLS is still unclear and may explain the nonsignificant correlation between the severity of skin disease and severity of oral infection [5, 7, 8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…In polymorphonuclear leucocytes (PMNs) of PLS patients, impaired chemotactic and phagocytic function and an impaired response to T and B cell mitogens have been reported (Roberts et al, ). Seren et al () recently reported that inactive cathepsin C could reduce the amount of membrane‐bound proteinase 3 (PR3 m ), a main target antigen of anti‐neutrophil cytoplasmic autoantibodies (ANCA), indicating a new treatment for granulomatosis with polyangiitis (GPA).…”
Section: Introductionmentioning
confidence: 99%